On Croatian Constitutional Identity and European Integration - Bačić, Petar (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This study addresses the topic of Croatian constitutional identity, which is firmly embedded in the original text of the Croatian Constitution adopted in 1990 and is closely connected to the European integration process from the inception of the existence of the Republic of Croatia as an independent and sovereign state. It analyses all relevant constitutional provisions that regulate the relationship between national and international law, including the constitutional amendments of 2010 adopted during Croatia’s European Union (EU) membership negotiations that refer to the modalities of accession, functioning of the Republic of Croatia in the EU, and adaptation of the Croatian legal system to new requirements stemming from the final stage of the European integration process. The position of the Croatian Constitutional Court regarding international and EU law and the question of transnational constitutional and judicial dialogue, in general, are also analysed. Entering the European Convention on Human Rights prompted the Constitutional Court to engage more actively in judicial dialogue with other courts. The Constitutional Court accepts and applies the legal standards developed by the European Court of Human Rights (ECtHR). Moreover, in its decisions, it often explicitly refers to the ECtHR case law and the case law of some European constitutional courts, following the pattern characteristic of judicial dialogue in Europe. The author notes that taking a position in such a transnational dialogue must be realised based on mutual partnership and respect. Finally, the elaboration of the fundamental values of constitutional order and the idea of European integration, with the parallel process of adaptation of the national constitutional-political system to the complex of European law, prompted the Constitutional Court of the Republic of Croatia to start developing the concept of constitutional identity.Keywords: constitution, identity, Republic of Croatia, national constitutional identity, Croatian Constitutional Court, constitutional dialogue